The concept of violence in modern political thought: Rousseau, the social contract and the preludes of revolutionary violence - Jiménez A., Javier (2016)
Using as a reference “The social contract” by J.J Rousseau, this paper aims to discern the theoretical/philosophical meaning of violence from his political perspective.